Methods for analyzing social media - Bredl, Klaus; Hunniger, Julia; Jensen, Jakob Linaa (London : Routledge, 2014)
The growth of social media invites many new questions such as: How can we analyze social media? Can we use traditional audience research methods and apply them to online content? Which new research strategies have been developed?
Includes bibliographical references and index.
Keywords: Social media -- Research -- Methodology